EVALUATION OF THE IMPACT OF ARTIFICIAL INTELLIGENCE ON EDUCATIONAL EQUALITY - Loso Judijanto; Erwin Yulianto; Andri Sungkowo (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
In this study, an assessment of the impact of artificial intelligence (AI) on educational equality was carried out. Through the analysis of literature and related research, the aim of this research is to identify how AI can contribute to improving accessibility, personalization, and equality in education. The research methods used involve searching for articles and scientific journals related to artificial intelligence and education, as well as in-depth analysis of such findings. The results of this study show that AI has great potential in supporting personalised learning approaches, reducing gaps in access to education, and identifying and addressing biases in the education system. Careful and sustained AI evaluation is important to ensure that the implementation of this technology has a positive impact on educational equality.